Racial/Ethnic Disparities of Cancer, Metabolic Syndrome, and Lifestyle Behaviors in People under 50: A Cross-Sectional Study of Data from the National Health and Nutrition Examination Survey - Lin Zhu; Areebah Rahman; Ming-Chin Yeh; Grace X. Ma (MDPI AG, 2022)
Introduction: Recent epidemiological studies have suggested a trend of increasing prevalence of metabolic syndrome (MetS) and certain types of cancer among adults under age 50. How MetS is associated with cancer in adults under the age of 50, however, remains unclear. Furthermore, it remains unknown whether associations between MetS and cancer vary by racial/ethnic group and whether modifiable lifestyle factors influence MetS-cancer relationships. Methods: We used data from the 2011-2018 National Health and Nutrition Examination Survey (NHANES) to define a case-control sample to examine potential racial/ethnic disparities associated with MetS and cancer of any type. We used a chi-square test and binary logistic regression to examine the MetS and cancer association. Results: From a total sample of 10,220 cases, we identified 9960 no-cancer cases and 260 cancer cases. Binary logistic regression results showed that MetS was significantly associated with a cancer risk among non-Hispanic whites (odds ratio = 1.48, 95% confidence interval = 1.00-2.19); however, it was not associated with a risk among non-Hispanic Blacks, Hispanic/Latinos, or Asian Americans. We also found several significant predictors of cancer, including age, gender, tobacco use, and sleep duration, with their roles varying by racial/ethnic subgroup. Conclusion: The findings of this study indicate that racial/ethnic differences are involved in the association between MetS and cancer, and highlight the potential mediating effects of lifestyle and behavioral factors. Future research should leverage the existing longitudinal data or data from cohort or case-control studies to better examine the causal link between MetS and cancer among racial/ethnic minorities.